Dynamics of adventitious rooting in mini-cuttings of Eucalyptus benthamii x Eucalyptus dunnii - doi: 10.4025/actasciagron.v34i2.13059 - Gilvano Ebling Brondani; Ivar Wendling; André Ebling Brondani; Marla Alessandra Araujo; André Luís Lopes da Silva; Antonio Natal Gonçalves (Acta Scientiarum. Agronomy, 2011)
It is possible to determine the optimum time for permanence of vegetative propagules (mini-cuttings) inside a greenhouse for rooting, and this value can be used to optimize the structure of the nursery. The aim of this study was to determine the dynamics of adventitious rooting in mini-cuttings of three clones of Eucalyptus benthamii x Eucalyptus dunnii. Sprouts of H12, H19 and H20 clones were collected from mini-stumps that were planted in gutters containing sand and grown in a semi-hydroponic system. The basal region of the mini-cuttings was immersed in 2,000 mg L-1 indole-3-butyric acid (IBA) solution for 10 seconds. The rooting percentage of the mini-cuttings, the total length of the root system and the rooting rate per mini-cutting were also evaluated at 0 (time of planting), 7, 14, 21, 28, 35, 42, 49 and 56 days. We used logistic and exponential regression to mathematically model the speed of rhizogenesis. The rooting percentage was best represented as a logistic model, and the total length of the root system was best represented as an exponential model. The clones had different speeds of adventitious rooting. The optimum time for permanence of the mini-cuttings inside the greenhouse for rooting was between 35 and 42 days, and varied depending on the genetic material.